(untitled) (Journal of Informatics Education and Research, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the global economy, contributing significantly to employment generation, innovation, and GDP growth. Despite their economic importance, MSMEs often face substantial barriers to accessing formal credit, with traditional financial institutions being reluctant to lend due to perceived high risks and lack of collateral. In recent years, fintech lending platforms have emerged as a disruptive force, offering innovative solutions to bridge the credit gap for MSMEs. This study investigates the role of fintech lending platforms in improving credit access for MSMEs, with a focus on understanding how technological advancements, risk mitigation strategies, and regulatory frameworks shape the MSME lending landscape. The research reveals that fintech platforms significantly outperform traditional banks in terms of loan approval rates, processing time, and disbursement speed. The findings show that fintech platforms leverage data-driven algorithms, which evaluate the creditworthiness of MSMEs using alternative data such as transactional history, social media activity, and e-commerce sales. The study identifies artificial intelligence (AI), machine learning (ML), blockchain, and alternative credit scoring models as the primary technologies driving the fintech lending revolution. AI and ML enhance the accuracy of credit risk assessments, while blockchain provides secure, transparent, and decentralized records of lending transactions. These technologies, combined with real-time transaction monitoring, enable fintech platforms to make faster and more informed lending decisions. The study demonstrates that these innovative risk mitigation strategies result in lower default rates compared to traditional lending models. However, the scaling of these platforms is contingent upon overcoming operational challenges and navigating complex regulatory landscapes. Future research should focus on the evolving regulatory environment and its impact on the sustainability and scalability of fintech lending models in emerging markets.